Individual and household exposures associated with cholera transmission in case–control studies: a systematic review. Issue 10 (1st September 2019) - Phelps, Matthew D.; Simonsen, Lone; Jensen, Peter K. M.
Abstract: Objective: Uncertainty persists regarding cholera transmission routes. We conducted a structured review of case–control studies on cholera transmission and provide a qualitative summary of reported exposures in order to inform public health efforts and future cholera research. Methods: We searched two electronic databases for published case–control studies that investigated risk factors for cholera and included any publications that did not match our exclusion criteria. From the included studies, we grouped exposures using two parameters, whether transmission domain was public or domestic, and also on the vehicle of transmission. We extracted data on study location, method of case and control inclusion, type of statistical analysis performed and which exposures were included. Additionally, two parallel subgroup analyses were performed. The first included the subgroup of all studies that used culture‐confirmed cholera cases, and the second included the subgroup of all studies employing a multivariate analysis. In the second analysis, we calculated the population attributable risk (PAR). Results: Our search yielded 2347 peer‐reviewed publications, of which 65 did not match our exclusion criteria, comprising 69 individual studies. Water‐based exposures were investigated in 97% of these studies, of which 70% found a significant association with cholera infection. Food‐based exposures were investigated in 75% of studies, of which 63% found a significant association with risk of cholera infection. Close personal contact with cholera cases was investigated in 30% of studies, of which 52% found a significant association with risk of cholera infection. Hygiene‐related exposures were investigated in 51% of studies, of which 63% found a significant association with cholera transmission. Among studies that examined at least one exposure related to the domestic domain, 76% found a significant association with cholera infection vs. 71% of studies investigating at least one public domain exposure. The subgroup analyses produced similar results. Conclusions: Despite strong evidence for cholera transmission via foodborne‐, hygiene‐, waterborne‐ and close personal contact‐related pathways in both domestic and public domains, we found that non‐waterborne‐related factors are understudied. Future cholera case–control studies would benefit from investigating all transmission vehicles and transmission domains. Abstract : Objectif: L'incertitude persiste quant aux voies de transmission du choléra. Nous avons mené une analyse structurée d'études cas‐témoins sur la transmission du choléra et fourni un résumé qualitatif des expositions rapportées afin d'éclairer les efforts de santé publique et les recherches futures sur le choléra. Méthodes: Nous avons recherché dans deux bases de données électroniques, des études cas‐témoins publiées, portant sur les facteurs de risque du choléra et avons inclus toutes les publications ne correspondant pas à nos critères d'exclusion. Parmi les études incluses, nous avons regroupé les expositions en utilisant deux paramètres, selon que le domaine de transmission soit public ou domestique, ainsi que sur le véhicule de transmission. Nous avons extrait les données sur le lieu de l'étude, la méthode d'inclusion des cas et des témoins, le type d'analyse statistique effectuée et les expositions incluses. En outre, deux analyses parallèles de sous‐groupes ont été effectuées. La première comprenait le sous‐groupe de toutes les études utilisant des cas de choléra confirmés par culture et la seconde, le sous‐groupe de toutes les études utilisant une analyse multivariée. Dans la seconde analyse, nous avons calculé le risque attribuable à la population. Résultats: Notre recherche a donné 2347 publications revues par des pairs, dont 65 ne correspondaient pas à nos critères d'exclusion et comprenant 69 études individuelles. Les expositions à base d'eau ont été investiguées dans 97% de ces études, parmi lesquelles 70% ont trouvé une association significative avec l'infection par le choléra. Les expositions d'origine alimentaire ont été investiguées dans 75% des études, dont 63% ont montré une association significative avec le risque d'infection par le choléra. Le contact personnel rapproché avec des cas de choléra a été investigué dans 30% des études, parmi lesquelles 52% ont trouvé une association significative avec le risque d'infection par le choléra. Les expositions liées à l'hygiène ont été étudiées dans 51% des études, dont 63% ont montré une association significative avec la transmission du choléra. Parmi les études portant sur au moins une exposition liée au domaine domestique, 76% ont trouvé une association significative avec l'infection par le choléra, contre 71% des études portant sur au moins une exposition du domaine public. Les analyses de sous‐groupes ont produit des résultats similaires. Conclusions: Malgré de solides preuves sur la transmission du choléra par des voies d'origine alimentaire, hygiénique, d'origine hydrique et de contact rapproché, dans les domaines domestique et public, nous avons constaté que les facteurs non liés à l'eau étaient peu étudiés. Les futures études cas‐témoins sur le choléra gagneraient à investiguer sur tous les véhicules et tous les domaines de transmission.